Produção de madeira de eucalipto de curta rotação em povoamentos adensados para energia - Moulin, Jordão Cabral (2013)
The study aimed to evaluate the influence of spacing, irrigation and harvesting age in wood production from 6 and 12-month-old clones of Eucalyptus grandis x Eucalyptus urophylla hybrid from irrigated and non-irrigated 3x0.5, 1.5x2, 3x1, 3x2 and 3x3 m spacing plantation. It was possible to verify the influence of spacing, irrigation and age in wood properties. The 12-month-old clone B from irrigated area and condensed spacing had higher wood volume. The clone A from large spacing had highest specific gravity. 12-month-old clones had less vessel frequency. 12-month-old clones from irrigated and smaller spacing area had higher fiber length. Thicker wall was found in 6-month-old clone A from non-irrigated area. 12-month-old clone B from irrigated area and greater spacing had higher lignin content. 12-month-old clone A from non-irrigated area and wider spacing has lower ash content